Evaluation of the relationship between NIRS (near-infrared spectroscopy) and optic nerve sheath diameter measurement in children with increased intracranial pressure: a pilot study - Didar Arslan; Dinçer Yıldızdaş; Özden Özgür Horoz; Nagehan Aslan; Faruk İncecik (BMC, 2021)
Abstract Background The increased intracranial pressure (ICP) syndrome may emerge depending on many different neurological factors and the early diagnosis and treatment are important for the prevention of neurologic damage and related mortality. In recent years, the follow-up of increased ICP with non-invasive methods has been rising. In this study, our objective was to determine the significance and any possible correlation between Optic Nerve Sheath Diameter (ONSD) and Near Infrared Spectroscopy (NIRS) in children with increased ICP. Methods Patients who were hospitalized in our pediatric ICU at Çukurova University Medical Faculty between June 2018 and June 2019 due to the suspicion of increased ICP were included in this study. The demographic characteristics of patients, diagnosis at admission, results of the cranial CT and MRI examinations, and results of the simultaneous ONSD and NIRS measurements were recorded. Results A total of 36 patients were included in our study. With respect to the diagnosis, non-traumatic causes were at the forefront in 30 patients (83.3%), and the most common causes were meningoencephalitis (n = 9; 25%) and non-traumatic bleeding (n = 7; 19.4%). Six of the patients were under the age of one year (16.7%), and the mean values of ONSD and NIRS were 4.8 ± 0.7 mm and 71.1 ± 12.4% respectively in this group. Fourteen patients were in the one to ten year age group and the mean values of ONSD and NIRS were 6.1 ± 0.6 mm and 72.7 ± 9.3% respectively. Sixteen patients were over ten years of age (44.4%), and the mean values of ONSD and NIRS were 5.6 ± 0.7 mm and 74.2 ± 16% respectively. There was no correlation between the ONSD and NIRS values (r:0.307; p = 0.068). Conclusion Our study showed that ONSD measurements were helpful in children with increased ICP and reflected the increase in ICP. However, our study also demonstrated that ONSD was not in correlation with the NIRS monitoring. We believe that there is a need for further studies focused on the use of ONSD and NIRS in the monitoring of increased ICP.